Central African Republic : 2016 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that economic growth in the Central African Republic has remained anemic since 2013 owing to structural rigidities, poor infrastructure, and limited energy supply. Inflation reached 11.6 percent in 2014 and receded to 4.5 percent in 2015 thanks to improved supply conditions and a fall in the prices of basic imports. Corrective measures implemented in 2015 allowed revenue to reach 7.1 percent. IMF Executive Directors have commended the authorities for the progress achieved under their economic program supported by the Rapid Credit Facility, which has helped stabilize the economy, rebuild core administrative capacity, and improve the management of public resources.